VARIASI BAHASA DALAM INTERAKSI SISWA DAN GURU BAHASA INDONESIA DI SMP PANGERAN ANTASARI MEDAN - Weni Tresya Girsang; Nanda Dwi Astri; Gumarpi Rahis Pasaribu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study, entitled “Language Variation in Interactions between Students and Indonesian Language Teachers at Pangeran Antasari Junior High School, Medan,” aims to describe the forms of language variation used in interactions between Grade IX-3 students and Indonesian Language teachers, as well as to identify the social and situational factors influencing the choice of language varieties during the Indonesian language learning process. The subjects of this study were Indonesian Language teachers and Grade IX-3 students of Pangeran Antasari Junior High School, Medan, in the 2025/2026 academic year. The object of the study was language variation in verbal utterances produced by teachers and students during classroom interaction. Data were collected through participatory observation, interviews, and documentation. This research employed a qualitative approach using the ethnography of communication. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was ensured through data triangulation and member checking. This study was conducted at Pangeran Antasari Junior High School, Medan, located on Jl. Veteran No. 1060/19, Helvetia. The findings revealed several forms of language variation, including formal, casual, intimate, and consultative varieties, with casual language being the most dominant form used by both teachers and students during classroom learning. Furthermore, social factors such as teacher–student social relationships, the teacher’s role as instructor and classroom manager, students’ age and characteristics, teacher–student closeness, and local social and cultural backgrounds, as well as situational factors including classroom conditions, communicative and instructional goals, classroom atmosphere, and types of learning activities, influenced the selection of language varieties used by teachers and students.